2020
DOI: 10.1038/s41377-020-0295-y
|View full text |Cite
|
Sign up to set email alerts
|

Spatial heterogeneity of oxygenation and haemodynamics in breast cancer resolved in vivo by conical multispectral optoacoustic mesoscopy

Abstract: The characteristics of tumour development and metastasis relate not only to genomic heterogeneity but also to spatial heterogeneity, associated with variations in the intratumoural arrangement of cell populations, vascular morphology and oxygen and nutrient supply. While optical (photonic) microscopy is commonly employed to visualize the tumour microenvironment, it assesses only a few hundred cubic microns of tissue. Therefore, it is not suitable for investigating biological processes at the level of the entir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(68 citation statements)
references
References 78 publications
(103 reference statements)
3
57
0
Order By: Relevance
“…Similarly, TUNEL is commonly used to quantify cell death within tumors exposed to various cancer treatments [ [51] , [52] , [53] ]. Along with H&E, these histological markers have been used successfully used to study the morphology of the tumor vasculature and cancer cells in studies involving PA imaging [ [54] , [55] , [56] ]. The H&E, TUNEL and CD31 sections were sequentially acquired within 10 μm of each other.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, TUNEL is commonly used to quantify cell death within tumors exposed to various cancer treatments [ [51] , [52] , [53] ]. Along with H&E, these histological markers have been used successfully used to study the morphology of the tumor vasculature and cancer cells in studies involving PA imaging [ [54] , [55] , [56] ]. The H&E, TUNEL and CD31 sections were sequentially acquired within 10 μm of each other.…”
Section: Methodsmentioning
confidence: 99%
“…From the above mentioned standpoint, the traditional anti-angiogenesis can deeply affect anti-tumour immunity, as full doses of drugs shrink the tumor, leading to cancer hypoxia and priming immune suppressive cells’ infiltration [ 160 ]. A wise use of therapeutic strategies halting the cancer angiogenesis must thus take into account the abnormal metabolic microenvironment characterizing a heterogeneous oxygenation [ 161 , 162 ]. Assessing oxygenation in the different layers of tumour pinpoint that there is a progressive increase of nutrient and oxygen levels across the inner depth [ 162 ], thus fueling genomic instability [ 163 ], the cancer progression (PD) [ 16 ], the switch to anaerobic metabolism [ 164 ], as well as the epithelial–mesenchymal transition, metastases [ 165 ], and the induction of cancer “stem cell” phenotype [ 166 ].…”
Section: Boosting Cancer Immunotherapy Using Anti-angiogenics: Thementioning
confidence: 99%
“…A wise use of therapeutic strategies halting the cancer angiogenesis must thus take into account the abnormal metabolic microenvironment characterizing a heterogeneous oxygenation [ 161 , 162 ]. Assessing oxygenation in the different layers of tumour pinpoint that there is a progressive increase of nutrient and oxygen levels across the inner depth [ 162 ], thus fueling genomic instability [ 163 ], the cancer progression (PD) [ 16 ], the switch to anaerobic metabolism [ 164 ], as well as the epithelial–mesenchymal transition, metastases [ 165 ], and the induction of cancer “stem cell” phenotype [ 166 ]. Hypoxia is a hallmark of cancer, inducing many abnormalities with prognostic consequences linked to defects in apoptosis and autophagy [ 167 , 168 ] and the resistance to radio-chemotherapy [ 169 , 170 , 171 ] and immunotherapy [ 13 , 172 , 173 ] likewise hamper the cancer aggressive phenotype acquisition, while shaping a pro-angiogenic, inflamed, and immunosuppressive neoplastic ecosystem [ 154 , 174 , 175 ].…”
Section: Boosting Cancer Immunotherapy Using Anti-angiogenics: Thementioning
confidence: 99%
“…Imaging hemoglobin with PAT can help to visualize the development of new vasculatures such as angiogenesis, which is a crucial parameter for early detection of tumor development [ 10 ]. Multiple studies had demonstrated the ability of PAT in early-stage cancer detection by monitoring the change in vasculature density [ 11 , 12 , 13 ]. Lin et al has demonstrated the use of a PACT system in detecting human breast tumor with a penetration depth of 4 cm within a single breath-hold [ 14 ].…”
Section: Endogenous Contrast Agentsmentioning
confidence: 99%